Simulation of System Dynamics for Improving The Quality of Paddy Production in Supporting Food Security - Mala Rosa Aprillya; Erma Suryani (Journal of Information Systems Engineering and Business Intelligence, 2023)
Background: The food security policy is an effort to ensure stable food availability and stable access of the community to food. As the population increases, this will affect the fulfillment of food needs in the future. Therefore, increase in rice production is needed to support food security. Objective: Conduct an analysis of the factors affecting the quality of rice production by using a dynamic system simulation that can be used as a basis for formulating policy strategies. Method: Simulation using System Dynamics (SD) is a method used to study and analyze complex systems by modeling non-linear behavior. Then several scenarios were carried out for the best decision-making using a computer. Result: The results of the scenario show that increasing the quality of paddy production in order to meet food needs in the future is doable by boosting the rendement of paddy as it will upgrade rice production which  will contribute greatly to rice production. Conclusion: From the simulation results, the  study can be used to increase the quality of rice production to maintain food security by improving the harvesting mechanism to increase yields. For further research, the use of Smart Agriculture can be considered to increase production of rice.   Keywords: Food security, Rice production, Rice production, System dynamics